Alternative-substitute business models and the provision of local infrastructure: Alterity as a solution to financialization and public-sector failure. Issue 95 (October 2018) - Bryson, John R.; Mulhall, Rachel A.; Song, Meng; Loo, Becky P.Y.; Dawson, Richard J.; Rogers, Christopher D.F.
Highlights: Local infrastructure and infrastructural exclusion. Alternative-Substitute Business Models to overcome infrastructural exclusion. Non-monetarised inputs and the provision of local infrastructure. An Alternative-Substitute Business Model conceptual framework. A dialogue between the business models, alterity and financialization debates. Abstract: Everyday living is supported by an array of services provided by a complex local infrastructure nexus that is financed and funded by the public, private and third sectors. The on-going debate on the financialization of infrastructure has neglected to explore the provision of local infrastructure in places experiencing infrastructural exclusion. This paper seeks to contribute toward filling this gap by exploring local infrastructure in the UK that has been provided by blending non-capitalist with capitalist activities. In other words, the provision of local infrastructure using an 'alternative' approach that attempts to address infrastructure exclusion by filling gaps in the provision of local infrastructure. The question is: how is infrastructure provided when it does not meet either a value for money calculation undertaken by the state or does not meet the investment criteria required by capital markets? This paper is the first to develop a dialogue between three unrelated literatures - financialization, business models and alterity – by developing a conceptual framework for exploring local infrastructure that is provided by alternative-substitute business models. The paper explores this approach through the analysis of two alternative infrastructure projects – Broadband 4 the Rural North and Malvern's heritage gas lamps.